The Correlation Between Body Mass Index and Body Fat Percentage in Menopausal Women in Padang: A Quasi-Experimental Study - Muarif Arhas Putra; Alficandra Alficandra; Lolia Manurizal; Joni Taufik Hidayat; Rahmah Evita Putri; Yovhandra Ockta (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
The global increase in overweight and obesity has become a critical public health concern, particularly among menopausal women who experience hormonal changes that contribute to increased body fat-especially in the abdominal region. High-Intensity Interval Training (HIIT) has emerged as a time-efficient alternative to conventional exercise, offering potential benefits in reducing Body Mass Index (BMI) and Body Fat Percentage (BFP). This quasi-experimental study, conducted in Padang, Indonesia, aimed to examine the correlation between BMI and BFP in menopausal women aged 50-60 years following a five-month HIIT intervention. A total of 50 obese menopausal women were selected using stratified sampling and assigned to either an experimental group (HIIT) or a control group (aerobic exercise). Pretest and posttest measurements were collected for body weight, BMI, and BFP. Statistical analyses included tests for normality and homogeneity, the Mann-Whitney U test, independent t-test, and Spearman's rank correlation. The findings revealed significant reductions in both BMI and BFP in the HIIT group compared to the control group. A very strong positive correlation was observed between BMI and BFP (r = 0.914, p < 0.001), suggesting that decreases in BMI are closely linked to reductions in body fat. This study provides preliminary evidence from Indonesia supporting HIIT as an effective and time-efficient intervention for addressing obesity-related outcomes in menopausal women. Further research is warranted to investigate the underlying mechanisms and to generalize these findings to broader menopausal populations. Keyword: High-Intensity Interval Training, Menopause, Body Mass Index, Body Fat Percentage, Obese Women.